2017
DOI: 10.1088/1742-6596/884/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

Dental erosion in 12-year-old school children living in Jakarta

Abstract: Abstract. This study assesses the dental erosion status of 12-year-old Indonesian children and studies the determinants of dental erosion of these children. The survey was performed in 2016 with ethics approval. A multistage cluster proportional to size random sampling method was adopted to select 12-year-old children in 24 primary schools in Jakarta. The parents were asked to complete a self-administered questionnaire concerning their children's diet and oral health habits. The children were examined by a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…Of these, questionnaires were validated for adolescents in only 11 studies, 28,34‐43 whereas the types of food/beverages evaluated were validated in five studies 44‐48 . Ten studies validated for both 49‐58 . Bivariate or multivariate analysis was conducted in all studies to determine statistical significance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, questionnaires were validated for adolescents in only 11 studies, 28,34‐43 whereas the types of food/beverages evaluated were validated in five studies 44‐48 . Ten studies validated for both 49‐58 . Bivariate or multivariate analysis was conducted in all studies to determine statistical significance.…”
Section: Resultsmentioning
confidence: 99%
“…Various types of tea were also examined with 11 studies reporting no significant link with DE; seven supported a significant increase in risk, 36,40,51,53,54,57,68 and one study reported a protective effect of tea following bivariate analysis 58 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it has been shown that parents' education level significantly affects the presence of oral disease in children [8]. A previous study assessed the status of dental erosion in a 12-year-olds in Jakarta-Indonesia, demonstrating that lower levels of parental dental knowledge, lower father's education, and being a girl were positively associated with dental erosion [9].…”
Section: Introductionmentioning
confidence: 95%